Determination of gonad reproductive state using non-lethal ultrasonography in endangered black (Haliotis cracherodii) and white abalone (H. sorenseni) - Boles, Sara E.; Rogers-Bennett, Laura; Bragg, Wendy K.; Bredvik-Curran, Jessica; Graham, Suzanne; Gross, Jackson A. (Frontiers in Marine Science, 2023)
Introduction Black (H. cracherodii) and white abalone (H. sorenseni) are federally listed as endangered species in the United States. Conservation efforts include captive breeding programs; however, determination of the reproductive state of individual abalone is notoriously difficult using traditional visual assessments. Ultrasonography is a well-recognized technology used to assess gonad reproductive condition accurately and nonlethally in cultured and wild fish, and more recently cultured red abalone (H. rufescens). Here, we implemented the use of ultrasound imaging technology to monitor the gonad condition of endangered black and white abalone. Methods Repeated ultrasound assessments of the gonad were used to assess seasonal changes in reproductive development in wild black (n=20), and captive white abalone (n=25). Results A modified ultrasound gonad index score was developed to incorporate multiple species of abalone. The ultrasound index scores ranged from one to five, with an index score of one being the lowest (gonad margin is thinly wrapped around the digestive gland or not present) and an index score of five being the highest (gonad margin is thick and significantly compressing the digestive gland). Conclusion We show that non-lethal ultrasound imaging technology is useful for tracking cyclical changes in the gonad reproductive condition as well as a more precise selection of individuals that are in peak reproductive condition for captive breeding programs.